Algumas gírias na língua de sinais brasileira - Dias, Beatriz Elisama Silva (Universidade Federal do Tocantins, 2022)
The description of slang for the linguistic studies of Libras is of great importance, since it allows to highlight and value the deaf culture and the lexical variants related to any language. Researching the linguistic field and choosing slang is a little widespread, more importante to deepen knowledge and register, not to reduce slang and deaf groups is naturally expressed. The research aims to analyze the deaf slang in Libras using linguistic contexto, in the perception of deaf people who live in Salvador-BA, Rio de Janeiro-RJ, Imperatriz-MA and Belém-PA. The methodology adopted by the work for the development of this work was exploratory research through interviews, the result was noticed that the slang is used with infinite aspects by the social groups of the deaf community.